Quantum photonic computer and its algorithms - Wan, Lingxiao (Nanyang Technological University, 2022)
Quantum information has been emerging as a fast-developing subject in recent years. It has shown the potential in bringing revolution to science and technology progress such as highly accurate and efficient simulation of practical physical systems, more compact and faster machine learning models for prediction and advanced quantum computational performance to solve intractable problems for classical supercomputers. Among many candidates to realize quantum technologies, the photon has demonstrated its prominent advantage for its robustness and ease of measurement. This thesis mainly focuses on the photonic integrated quantum technologies to produce and manipulate photons on an integrated silicon chip and characterizes its performance along with the demonstration of three quantum computing: GBS quantum computing for the perfect matching problem, quantum error correction and quantum teleportation with autoencoder. The theoretical modeling, photonic integrated circuit design and experimental implementation process are described detailly in this thesis.